A study on the factors affecting customer’s confidence towards product with Halal logo / Muhammad Farid Harith - Harith, Muhammad Farid (Faculty of Business and Management, Universiti Teknologi MARA, 2014)
The purpose of this study was to investigate the relationship of the selected independent variables: packaging, company, media and religiosity with dependent variable which is the affecting customer’s confidence toward product with Halal logo. In order to provide a guide in the study, four hypotheses were formulated. Data were collected from 100 respondents using the questionnaire. This study was conducted at Bandar Melaka. Then the results was analysed by using SPSS to find the significant relationship with the dependent variables. Through this study, it will help the us to understanding the factor why customer more confident's toward Halal logo on the product.